Hypoxemia With Pneumonia In Under Five Children: A Hospital-based Study In Dhaka, Bangladesh (Bangladesh Journal of Medicine, 2025)
Background: Pneumonia causes significant child morbidity and mortality globally, especially in developing countries. Hypoxemia is a critical complication in pediatric pneumonia and a key indicator of severe disease needing urgent medical intervention. This study aimed to investigate the clinical predictors of hypoxemia in children with pneumonia. Methods: This is a cross-sectional comparative study was conducted at Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh, from January to December 2022. A total of 394 children aged 2-59 months with pneumonia were purposively enrolled. Of these, 132 (33.5%) had hypoxemia, while 262 (66.5%) did not. All demographic, diagnostic, and clinical data were recorded and analyzed usingSPSS version 22.0. Results: In univariate analysis, hypoxic status correlated significantly with vomiting, fast breathing, inability to drink, unusual sleepiness(p